The Effect of PVC Powder content on the Elastic Moduli and Acoustic Impedance of Epoxy Composites - Majeed, Kawakib Jassim (Iraqi Journal of Physics, 2009)
The primary purpose of the present research was to study the effect of polyvinyl chloride (PVC) powder content on ultrasonic wave velocity in PVC/Epoxy composites. The second part is concerned with the relations of dynamic elastic moduli with the ultrasonic wave velocities, to determine how ultrasonic waves can affect them.Experimental data have been obtained using the sonic viewer (model -5217 A) device to generate two types of waves, longitudinal waves of frequency 63 kHz and transverse waves of frequency 33 kHz and to measure the transit time required for those waves to travel through individual sample.The experimental results have shown that the propagation of the ultrasonic velocity increases directly with PVC content in the tested specimens, due to the changes in the dynamical properties that were investigated from the calculated values of the elastic moduli of the composites